Comparison of techniques for culture of dialysis water and fluid. Issue 2 (5th September 2016) - Maltais, Jo‐Ann B.; Meyer, Klemens B.; Foster, Meredith C.
Abstract: Introduction: Microbiological culture of dialysis water and fluid is a routine safety measure. In the United States (U.S.), laboratories perform these cultures on trypticase soy agar at 35–37°C for 48 h (TSA‐48h), not on the tryptone glucose extract agar or Reasoner's 2A agar at 17–23°C for 7 days (TGEA‐7d and R2A‐7d, respectively) recommended by international standards. We compared culture methods to identify samples exceeding the accepted action level of 50 CFU/mL. Methods: Dialysis water and fluid samples collected from 41 U.S. dialysis programs between 2011 and 2014 were cultured at two U.S. laboratories. Each sample was cultured using (1) either TGEA‐7d or R2A‐7d and (2) TSA‐48h. We compared proportions exceeding the action level by different methods and test characteristics of TSA‐48h to those of TGEA‐7d and R2A‐7d. Findings: The proportion of water samples yielding colony counts ≥50 CFU/mL by TGEA‐7d was significantly different from the proportion by TSA‐48h (P = 0.001; difference in proportion 4.3% [95%CI 1.3–7.3%]). The proportions of dialysis fluid samples ≥50 CFU/mL by TGEA‐7d and TSA‐48h were not significantly different; there were no significant differences for comparisons of R2A‐7d to TSA‐48h. Discussion: In dialysis fluid, TSA‐48h was comparable to TGEA‐7d and R2A‐7d in identifying samples as having bacterial counts ≥50 CFU/mL. In dialysis water, TSA‐48h was comparable to R2A‐7d in identifying samples ≥50 CFU/mL, but TGEA‐7d did yield significantly more results above 50 CFU/mL. Nonetheless, the negative predictive value of a TSA‐48h result of <50 CFU/mL in dialysis water exceeded 95%.